Engineering Ligand and Receptor Pairs with LIPSTIC to Track Cell‐Cell Interactions. Issue 12 (6th December 2021) - Alberti, Dafne; Guarniero, Michelle; Maciola, Agnieszka K.; Dotta, Enrico; Pasqual, Giulia
Abstract: Interactions between different cell types are critical for a plethora of biological processes, such as the immune response. We recently developed a novel technology, called LIPSTIC (labeling of immune partnership by SorTagging intercellular contacts), that allows for identifying cells undergoing specific interactions thanks to an enzymatic labeling reaction. Our work demonstrated the use of this technology to monitor interactions between immune cells, both in vitro and in vivo, by the genetic engineering of CD40 and CD40L, an essential costimulatory axis between antigen‐presenting cells and T cells. Here we describe protocols to design novel LIPSTIC‐engineered ligand and receptor pairs, clone constructs into retroviral expression vector, perform their initial validation, and use them to measure interactions ex vivo. This information will be useful to investigators interested in exploiting the LIPSTIC technology to track their favorite immune interaction. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 16, 2022, after first online publication: CRUI‐CARE funding statement has been added.] Basic Protocol 1 : Design of LIPSTIC‐engineered ligand and receptor pairs Basic Protocol 2 : Cloning of LIPSTIC‐engineered ligand and receptor pairs Basic Protocol 3 : Validation of LIPSTIC‐engineered ligand and receptor pairs in 293T cells Basic Protocol 4 : Measuring interaction with LIPSTIC in immune cells ex vivo